2017
DOI: 10.1007/s11914-017-0382-z
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome and Bone: to Build, Destroy, or Both?

Abstract: Purpose of the Review The gut microbiota can be considered a hidden organ that plays essential roles in host homeostasis. Exploration of the effects of microbiota on bone have just begun. Complimentary studies using germ-free mice, antibiotic and probiotic treatments reveal a complicated relationship between microbiota and bone. Here we review recent reports addressing the effect of gut microbiota on bone health, discuss potential reasons for discrepant findings, and explore potential mechanisms for these effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 54 publications
2
69
0
1
Order By: Relevance
“…More and more studies have shown that the intestinal flora may regulate the immune system and endocrine system through the gut-brain axis to participate in the body's bone metabolism. The imbalance of gut microbiome can cause the imbalance of osteogenesis and osteoclast reaction and cause osteopenia, while the specific mechanism has not been determined (Ohlsson and Sjögren, 2015;Yan and Charles, 2017;Ibáñez et al, 2019). As far as we know, there are few studies on the relationship between intestinal flora and osteoporosis, we characterized the disease-related microbiota by 16s rDNA Amplicon Sequencing, proving that there are possible biomarkers (including microbial composition and function) in gut microbiome group in patients with PO.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…More and more studies have shown that the intestinal flora may regulate the immune system and endocrine system through the gut-brain axis to participate in the body's bone metabolism. The imbalance of gut microbiome can cause the imbalance of osteogenesis and osteoclast reaction and cause osteopenia, while the specific mechanism has not been determined (Ohlsson and Sjögren, 2015;Yan and Charles, 2017;Ibáñez et al, 2019). As far as we know, there are few studies on the relationship between intestinal flora and osteoporosis, we characterized the disease-related microbiota by 16s rDNA Amplicon Sequencing, proving that there are possible biomarkers (including microbial composition and function) in gut microbiome group in patients with PO.…”
Section: Discussionmentioning
confidence: 88%
“…Studies have shown that abnormal gut microbiome is associated with more and more health status (Sekirov et al, 2010;Kundu et al, 2017;Song et al, 2018). Related basic and clinical studies have shown that gut microbiome may be involved in bone metabolism through gut-brain axis regulation of immune system, endocrine system, and so on (Ohlsson and Sjögren, 2015;Yan and Charles, 2017;Ibáñez et al, 2019). A large number of studies have shown that there is an interaction between solid hormones and gut microbiome (Baker et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This increase in bone density was attributed to a decrease in osteoclast, as well as, inflammatory cytokines in the bone and bone marrow in the germ free mice vs conventionally raised mice [132]. However, the effects of microbiome on bone density, as determined by studies using germ free mice, are not consistent across mouse strains and/or sex [136][8][130][132]. In addition, the impact of the microbiota changes on the epithelial barrier were not been fully examined.…”
Section: Barrier Pathophysiology In Diseasementioning
confidence: 99%
“…There are mixed findings regarding the bone phenotype of germ-free mice. Germ free mice may have increased bone mass/density or reduced bone mass/density compared to conventionally raised animals [29, 30, 11, 31]. A major challenge in interpreting differences among studies of germ free mice is that the studies are not consistent in terms of mouse strain, sex or age.…”
Section: Bonementioning
confidence: 99%